Magnesium promoted hydrocalumite derived nickel catalysts for ethanol steam reforming. (30th April 2023) - Liu, Hongrui; Ding, Rui; Zhang, Yuguang; Li, Hongshen; Li, Shizhong
Abstract: Hydrocalumite derived nickel (Ni) catalysts with different loading of magnesium (Mg) (7.5/10/15 wt%, as promoters) were for the first time prepared and tested for ethanol steam reforming (ESR) in this work. The catalytic performances of different Mg promoted catalysts were mainly evaluated in the temperature range between 550 and 700 °C as determined by thermodynamic simulation. Experimental results showed that the optimal reaction temperature was 650 °C in terms of the hydrogen yields for these ESR catalysts, especially for 15Ni7.5Mg/HCa which presented a remarkable catalytic performance. Its hydrogen yields reached 90% while ethanol was almost fully converted at 650 °C. Based on the characterization results, it's believed that 15Ni7.5Mg/HCa with a certain amount of Mg loading can get the smallest Ni 0 crystallite sizes, better H2 reducibility and suitable basicities on strong basic sites. The catalytic performances of ESR catalysts were mainly related to the Ni 0 crystallite size, reducibility and basicity for the prepared hydrocalumites derived Ni catalysts, and 15Ni7.5Mg/HCa could be considered as one of the best catalysts for ESR. Graphical abstract: Image 1 Highlights: Mg promoted hydrocalumite derived Ni catalysts for ethanol steam reforming. Influence of variable Mg on physicochemical properties and activities. Mg leads to more adequate reduction and smaller Ni 0 crystallite sizes. 100% C2 H5 OH conversions, 90% H2 yield.